Implementation of the Improvement Program in Mathematics for Class V Students at State Elementary School (SDN) 3 Sepit - Sri Astuti; Arini Hariyati (Tinta Emas Publisher, 2023)
This type of research is descriptive qualitative research, namely a study aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually or in groups. The purpose of this study was to find out the implementation of the improvement program in the mathematics subject for fifth grade students at SDN 3 Sepit for the 2022/2023 academic year. Methods of data collection using tests, observations, interviews and documentation. While the data analysis technique uses a credibility test (trust) with a triangulation technique. The results of the research show that in the improvement activities, the researchers have carried out the repairs to the maximum, while the results achieved from these activities have been proven by the results of these activities. Students who previously received grades that had not yet reached the KKM, but after the improvement activities were held the student scores proved to have increased, and most of the students who were given improvement activities experienced increased learning outcomes